The Complexity of Competition, Business Strategy and Corporate Tax Aggressiveness in Indonesia - Arieftiara, Dianwicaksih; Widiastuti, Ni Putu Eka; Andriyanto, Wahyu Ari (International Journal of Psychosocial Rehabilitation, 2020)
Manuscript type: Research paper The research aims: This study aims to investigate how managers’ behavior in avoiding taxes if the company implements a certain business strategy and faces different competition intensities. The top management’s decision in choosing a business strategy becomes a reference for top managers to carry out corporate management. This condition of environmental uncertainty can also affect the intensity of tax aggressiveness of each company following the business strategy group. Design / Methodology / Approach: This study was conducted using quantitative methods in going public companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sampling method used was purposive non-probability sampling, with several criteria, which are the manufacturing companies listed on the Exchange Indonesian Securities in 2014 to 2018, possess a complete financial report and the required data is widely available, from 2009 to 2018 (for the needs of business strategy variable data). The measure of tax aggressiveness uses the Latent Variable Factor Score through Confirmatory Factor Analysis (CFA). The model used in testing the hypothesis is multiple linear regression models and multiple linear regression models with moderated multiple regression.` Research findings: In the context of this study, which is in manufacturing companies from 2014 to 2018, if it is compared to analyzer companies, the aggressiveness of defender tax has not been proven to be lower. This can be caused by tax aggressiveness not being proven to be a defender’s choice, but that does not mean that the defender is not doing his tax planning. The complexity of the competition enlarges the level of tax avoidance carried out by the prospector compared to the analyzer. Besides, the test results show evidence that the complexity of competition has a positive effect on the level of tax avoidance committed by the defender compared to the analyzer. Furthermore, other results show that the complexity of competition increases the level of tax avoidance carried out by the prospector compared to the defender. Theoretical contribution / Originality: This study providing empirical evidence that the tax behavior of managers for each business strategy group (defender, prospector and analyzer) can be different. In a business strategy group, managers can differ in their level of tax aggressiveness even though they have a similar type of strategy. In the conditions of high competition complexity, a strategy can change its tax behaviour. It is different if compared to the condition where the company is in a low competition complexity. Practitioner / Policy implication: Tax aggressiveness is one level in tax avoidance. Defender companies are companies that focus on low costs and avoid risks and proven in the high complexity of competition, defenders avoid higher taxes than analyzers. Although tax aggressiveness is a legal tax avoidance effort, defender managers must pay attention to their level of aggressiveness so as not to create potential sanctions / risks especially if the company faces a condition of high competition complexity. Research limitation / Implication: This study has a weakness which is using the Herfindahl index measure in measuring the complexity of competition. It is because the only available market share data is only data available on public companies. Therefore, herfindhal index in this study is only able to know the complexity of competition in companies that trade their shares on the IDX in the same industry. This happens because of limited data sources, so far there is no complete data regarding the total market share of all companies in the industry in Indonesia.